Communication audit on Barangay Mintal's Solid Waste Disposal Guide a readability study - Luz, Ann Marjorie F.
This study aims to evaluate the readability level of the Solid Waste Disposal Guide of Barangay Mintal. The study made used of the communication audit and readability study (Gunning Fox Index) to measure the disposal guide's readability level. Readability of material refers to the degree of easiness of a reading text. Classic studies measured readability based o formula. On the other hand, the new wave of readability studies also known as the new readability studies made used the reader's ability to assess readability level of a given text. This was due to the fact the readers were the ones who would decide on the material's readability. This study showed that laws were not institutionalized because of the provisions level of readability. The gatekeepers such as the barangay were responsible in making the ordinance easier to comprehend. The solid waste disposal guide of Barangay Mintal showed that the barangay was not able to edit and make specific provisions readable. This caused a low readability level on the disposal guide. Based on the demographic analysis that the researcher conducted, majority of the readers may not find the disposal guide understandable causing a pre-judged bias on the readers end. Hence, the barangay should recognized the ability of the readers to tailor a solid waste disposal guide that is comprehensible and readable